Myoglobin‐mediated lipid shuttling increases adrenergic activation of brown and white adipocyte metabolism and is as a marker of thermogenic adipocytes in humans. Issue 12 (8th December 2022) - Christen, Lisa; Broghammer, Helen; Rapöhn, Inka; Möhlis, Kevin; Strehlau, Christian; Ribas‐Latre, Aleix; Gebhardt, Claudia; Roth, Lisa; Krause, Kerstin; Landgraf, Kathrin; Körner, Antje; Rohde‐Zimmermann, Kerstin; et al.
Abstract: Background: Recruitment and activation of brown adipose tissue (BAT) results in increased energy expenditure (EE) via thermogenesis and represents an intriguing therapeutic approach to combat obesity and treat associated diseases. Thermogenesis requires an increased and efficient supply of energy substrates and oxygen to the BAT. The hemoprotein myoglobin (MB) is primarily expressed in heart and skeletal muscle fibres, where it facilitates oxygen storage and flux to the mitochondria during exercise. In the last years, further contributions of MB have been assigned to the scavenging of reactive oxygen species (ROS), the regulation of cellular nitric oxide (NO) levels and also lipid binding. There is a substantial expression of MB in BAT, which is induced during brown adipocyte differentiation and BAT activation. This suggests MB as a previously unrecognized player in BAT contributing to thermogenesis. Methods and Results: This study analyzed the consequences of MB expression in BAT on mitochondrial function and thermogenesis in vitro and in vivo. Using MB overexpressing, knockdown or knockout adipocytes, we show that expression levels of MB control brown adipocyte mitochondrial respiratory capacity and acute response to adrenergic stimulation, signalling and lipolysis. Overexpression in white adipocytes also increases their metabolic activity. Mutation of lipid interacting residues in MB abolished these beneficial effects of MB. In vivo, whole‐body MB knockout resulted in impaired thermoregulation and cold‐ as well as drug‐induced BAT activation in mice. In humans, MB is differentially expressed in subcutaneous (SC) and visceral (VIS) adipose tissue (AT) depots, differentially regulated by the state of obesity and higher expressed in AT samples that exhibit higher thermogenic potential. Conclusions: These data demonstrate for the first time a functional relevance of MBs lipid binding properties and establish MB as an important regulatory element of thermogenic capacity in brown and likely beige adipocytes. Abstract : Myoglobin (MB) is highly expressed in brown adipose tissue (BAT), its expression level increases with adipocyte differentiation and it is temperature dependently regulated in vivo. Expression levels of MB in brown and white adipocytes control mitochondrial respiratory capacity and increase acute response to adrenergic signalling and lipolysis. Effects of MB in adipocytes seem mainly mediated by its interaction with lipids to increase substrate flux to mitochondria. In mice, whole‐body knockout of MB results in impaired thermoregulation and BAT activation. In human white adipose tissue depots, MB is differentially expressed in obesity and correlates with markers of AT browning.